The Effectiveness of Developing Motor Skills Through Motion-Based Video Gaming: A Review. (December 2017) - Jenny, Seth E.; Schary, David P.; Noble, Kristy M.; Hamill, Shelley D.
Background. Technology growth affords innovative teaching techniques as video gaming within education has increased in popularity.Motion-based video gaming (MBVG) is a type of gaming that requires the individual playing the game to be physically interactive. Thus, whatever movements the individual playing the game does is picked up by motion sensors and is mimicked via the on-screen character. MBVG provides constant feedback to learners and has been found to help motivate students, replace sedentary with active gaming, and can facilitate social interactions with peers. Aim. This literature review reveals the current knowledge regarding the potential educational benefits of MBVG, particularly inphysical education andsport pedagogy settings. Developments of video gaming in education as well as recent research regarding MBVG and its potential impact on physicalskill development within educational environments are discussed. Conclusion. MBVG may be beneficial with novices in teaching basic sport concepts or with individuals with special needs who might otherwise not be able to participate in the full authentic version of the sport. However, empirical evidence is lacking which supports the effective use of MBVG in accuratelyteaching authentic sport-specific motor skills.